- EMERGENCE OF NIPAH VIRUS: A REVIEW - Adiga, Rama - (Journal of Biomedical and Pharmaceutical Research, 2019)
An emerging zoonotic infection caused by Nipah virus has become a Biosafety Level-4 pathogen capable of causing infection in animals and man. Bats belonging to Pteropodidae family, genus Pteropus which constitute fruit bats are the host reservoirs. Genus Eidolon constituting nonpteropid bats were later found to contain the virus. Genetic and molecular similarities between Nipah and Hendra viruses helped their classification into a new genus of Henipavirus.The first reported outbreak of Nipah disease from Malaysia took place in 1998.Two genetic strains of Nipah have been identified in Asia which are of severe and less severe forms. Surveillance should be upgraded and more research focussing on Nipah were envisaged in the blueprint published by WHO.